SCORING ANALYSIS OF THE RELATIONSHIP BETWEEN MAGNETIC RESONANCE IMAGING- ANXIETY QUESTIONNAIRE (MRI-AQ) WITH HEART RATE TO PATIENTS ANXIETY LEVEL AT LUMBOSACRAL MRI EXAMINATION - Amaliya, Mirza Isna; Setiawati, Rosy; Sari, Amillia Kartika; Muqmiroh, Lailatul; Muhaimin, Muhaimin (Faculty of Vocational Studies, Universitas Airlangga, 2019)
Background: Anxiety during MRI examination becomes a common constraint and can have a negative effect that is the quality of the resulting image due to the existence of motion artifacts until the failure of the examination. Purpose: One of the signs of anxiety can be seen an increase in heart rate, in addition there is one questionnaire specifically aimed to determine the level of anxiety in patients with MRI examination, namely Magnetic Resonance Immunization-Anxiety Quistionnaire (MRI-AQ). Method: This research used correlational method with cross-sectional approach. The sampling technique used is purposive sampling. In this research, there were 30 samples. Each sample will be measured heart rate before, during, and after Lumbosacral MRI examination. A Magnetic Resonance Imaging Anxiety Questionnaire (MRI-AQ) was then completed at the time of examination. Collected data were then tested for differences using paired-t test and pearson correlation test. Result: The result of paired-t test shows that there was difference of heart rate during and after examination with p-value 0,036 <α. The patient's heart rate during Lumbosacral MRI was higher than the patient's heart rate after Lumbosacral MRI at 85.63 bpm ± 14.709. Conclusion: Pearson correlation test results showed a correlation between Magnetic Resonance Imaging- Anxiety Questionnaire (MRI-AQ) with heart rate to patient anxiety level at Lumbosacral MRI Examination, this is reinforced by correlation value r = 0.636.